The Influence of Hospital Services, Quality Of Hospital and Medical Personnel Toward Patient's Intentions on Treatment in Malaysia For Hospital Policy in Indonesia and Malaysia - Purwatiningsih, Annisa; Fianto, Latif; Masykur, Lisa Dhuhaniyati (REFORMASI, 2024)
Health is a basic need for people from the lower classes to the upper classes. Health services by private hospitals, especially both in Indonesia and abroad, are a factor in the success of the hospital in providing medical services for patients. With the best hospital services in Indonesia, it reduces the patient's desire to seek treatment abroad. This is a form of competition for hospital services between Indonesia and Malaysia. Continuously, hospital services and professional medical personnel with international standard training in Malaysia have increased every year following the development of health problems and medical technology. The promotion of hospitals in Malaysia is increasing for the care of Indonesian patients and an increase in the number of Indonesian patients who are recommended to seek treatment in Malaysia. The results showed that the quality factor of medical personnel in Malaysia had the greatest influence on the perception of hospital services and the quality of the hospital on the intention to seek treatment in Malaysia.AbstrakKesehatan merupakan kebutuhan dasar bagi masyarakat dari lapisan bawah hingga lapisan atas. Pelayanan kesehatan yang dilakukan oleh rumah sakit swasta khususnya baik di Indonesia maupun di luar negeri menjadi salah satu faktor keberhasilan rumah sakit dalam memberikan pelayanan medis kepada pasien. Dengan adanya pelayanan rumah sakit terbaik di Indonesia mengurangi keinginan pasien untuk berobat ke luar negeri. Hal ini merupakan bentuk persaingan pelayanan rumah sakit antara Indonesia dan Malaysia. Pelayanan rumah sakit dan tenaga medis profesional dengan pelatihan berstandar internasional di Malaysia terus meningkat setiap tahunnya seiring dengan perkembangan permasalahan kesehatan dan teknologi kedokteran. Promosi rumah sakit di Malaysia semakin meningkat untuk perawatan pasien Indonesia dan peningkatan jumlah pasien Indonesia yang direkomendasikan untuk berobat di Malaysia. Hasil penelitian menunjukkan bahwa faktor kualitas tenaga medis di Malaysia mempunyai pengaruh paling besar terhadap persepsi pelayanan rumah sakit dan kualitas rumah sakit terhadap niat berobat di Malaysia.